Oxidative potential and chemical composition of PM2.5 in office buildings across Europe – The OFFICAIR study. (July 2016) - Szigeti, Tamás; Dunster, Christina; Cattaneo, Andrea; Cavallo, Domenico; Spinazzè, Andrea; Saraga, Dikaia E.; Sakellaris, Ioannis A.; de Kluizenaar, Yvonne; Cornelissen, Eric J.M.; Hänninen, Otto; Peltonen, Matti; Calzolai, Giulia; et al.
Abstract: In the frame of the OFFICAIR project, indoor and outdoor PM2.5 samples were collected in office buildings across Europe in two sampling campaigns (summer and winter). The ability of the particles to deplete physiologically relevant antioxidants (ascorbic acid (AA), reduced glutathione (GSH)) in a synthetic respiratory tract lining fluid, i.e., oxidative potential (OP), was assessed. Furthermore, the link between particulate OP and the concentration of the PM constituents was investigated. The mean indoor PM2.5 mass concentration values were substantially lower than the related outdoor values with a mean indoor/outdoor PM2.5 mass concentration ratio of 0.62 and 0.61 for the summer and winter campaigns respectively. The OP of PM2.5 varied markedly across Europe with the highest outdoor OP AA m −3 and OP GSH m −3 (% antioxidant depletion/m 3 air) values obtained for Hungary, while PM2.5 collected in Finland exhibited the lowest values. Seasonal variation could be observed for both indoor and outdoor OP AA m −3 and OP GSH m −3 with higher mean values during winter. The indoor/outdoor OP AA m −3 and OP GSH m −3 ratios were less than one with 4 and 17 exceptions out of the 40 cases respectively. These results indicate that indoor air is generally less oxidatively challenging than outdoors. Correlation analysis revealed that trace elements play an important role in determining OP, in particular, the Cu content. Indoor air chemistry might affect OP since weaker correlations were obtained for indoor PM2.5 . Our findings also suggest that office workers may be exposed to health relevant PM constituents to a different extent within the same building. Highlights: PM2.5 mass concentration and oxidative potential (OP) varied markedly across Europe. The I/O PM2.5 mass concentration ratio was less than one with two exceptions. Generally, it is better to stay indoors than outdoors regarding particulate OP. OP metrics were associated mainly with traffic-related trace elements (e.g., Cu). Indoor air chemistry may play an important role in the OP of indoor PM.